Investigation of physical and chemical properties and structure of tripolyphosphate coatings on zinc plated steel - Vlasova, Olena; Kovalenko, Vadym; Kotok, Valerii; Vlasov, Sergey; Cheremysinova, Anna (Eastern-European Journal of Enterprise Technologies, 2017)
The results of complex studies on the influence of the concentration of aqueous sodium tripolyphosphate solution on the physicochemical properties and structure of the coats on zinc-plated steel are presented. The coats were chemically deposited from 2–14 % aqueous sodium tripolyphosphate (STPP) solutions, heated to 70 ºС. It has been established that increasing concentration of aqueous STPP solution leads to an increase of the specific mass and crystallinity of the coats and decrease of protective properties. Metallographic studies have shown that the amorphous structure of the coats deposited from 2 % aqueous STPP solution changes to a structure with large sizes of crystallites for the coats prepared from aqueous STPP solutions with higher concentrations. The results of the X-ray diffraction (XRD) analysis have revealed that the coats with low protective properties, in addition to anhydrous zinc phosphates, also contain hydrated species. By means of raster electron microscopy, it has been established that the coats with the lowest protective properties, prepared from 12–14 % aqueous STPP solutions, are formed as thick, spongy layers with the presence of microcracks. Such structure leads to the accumulation and containment of moisture, which promotes corrosion under atmospheric conditions.